The roles of competition and climate in tree growth variation in northern boreal old‐growth forests. (19th November 2018) - Aakala, Tuomas; Berninger, Frank; Starr, Mike
Abstract: Questions: How have tree growth and growth trends varied in structurally complex old‐growth forests? What determines this variation and how this differs among species? Location: Natural boreal old‐growth forests, northern Finland. Methods: We sampled trees over 10‐cm diameter on 48 randomly located 0.1‐ha plots in three landscapes and compiled a data set of 1, 565 trees including all three main species, and a full range of sizes and competitive states in northern boreal old‐growth forests. We extracted tree ring samples from every tree and used ring widths to reconstruct tree sizes and their neighbourhood for the past 50 years for Pinus sylvestris and Picea abies, and 30 years for Betula pubescens . We used mixed‐effects models to study variation in tree growth. In the models, we used annually varying environmental variables, forest and tree structural variables and site variables as predictors. We also measured soil hydraulic properties for a water balance model to specifically include soil moisture deficits as predictors. Results: Tree growth rates had increased during the analysis period for all three species, with the highest increases for P. sylvestris and B. pubescens . All three species grew well during warm summers, but P. sylvestris and P. abies growth was also negatively influenced by soil moisture deficits. Competition in these sparse forests had a small influence on growth. However, its influence increased over time. Conclusions: The trees showed positive growth trends, but the increasing competition means that such strong positive trends are unlikely to continue over the long term. For year‐to‐year variability, negative influence of droughts implied that increasing temperatures are not only beneficial to tree growth even in these high‐latitude forests. Overall, the findings demonstrate the site‐ and species‐dependent complexity in tree responses to environmental and structural changes we may expect in the future. Abstract : Tree growth rates in the northern boreal old‐growth forests in Finland showed increasing trends in the recent decades. However, at annual resolution, droughts negatively influenced the growth of Norway spruce and Scots pine, implying that even in these high latitude (67°N) forests the benefits of increasing temperatures to tree growth are limited.